1995
DOI: 10.1113/jphysiol.1995.sp020604
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor modulation of cutaneous vasodilator and sudomotor responses to thermal stress in humans.

Abstract: 1. The influence of baroreceptor unloading on cutaneous vasodilatation was investigated in ten human subjects during dynamic supine cycle ergometer exercise at 28 degrees C. Increases in forearm skin blood flow (venous occlusion plethysmography) and arterial blood pressure (non-invasive) were measured and used to calculate forearm vascular conductance while local chest sweating rate was measured by dew-point hygrometry. Subjects performed two similar exercise protocols with and without baroreceptor unloading i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 28 publications
8
82
5
Order By: Relevance
“…Given previous findings that demonstrate a relationship between muscle metaboreceptor stimulation and the elevation in blood pressure and muscle sympathetic nerve activity during post-exercise ischaemia (Victor et al 1988;Nishiyasu et al 1994), it is clear that muscle metaboreceptors during post-exercise ischaemia were activated in the present procedure. Since baroreceptors have been shown to modulate sweat rate (Mack et al 1995), it was possible Role of metaboreflex and/or baroreflex on sweating J. Physiol. 534.2 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given previous findings that demonstrate a relationship between muscle metaboreceptor stimulation and the elevation in blood pressure and muscle sympathetic nerve activity during post-exercise ischaemia (Victor et al 1988;Nishiyasu et al 1994), it is clear that muscle metaboreceptors during post-exercise ischaemia were activated in the present procedure. Since baroreceptors have been shown to modulate sweat rate (Mack et al 1995), it was possible Role of metaboreflex and/or baroreflex on sweating J. Physiol. 534.2 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this increase in sweating was attributed to muscle metaboreceptor simulation since sweat rate remained elevated during post-IHG exercise ischaemia under moderately warmed and hyperthermic conditions (Crandall et al 1998;Kondo et al 1999). However, given prior findings that baroreceptors modulate sweating (Mack et al 1995), coupled with elevations in mean arterial blood pressure during exercise and post-exercise ischaemia, it may be that baroreceptor loading contributes to increases in sweat rate during IHG exercise and post-exercise ischaemia. To our knowledge, the contribution of elevated arterial blood pressure during exercise on the control of sweat rate remains unknown.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Fortney et al 16) examined the effect of isotonic hypovolemia by 9% on local SR during exercise at 65-70% of VO 2max in a hot environment (T a =30°C, relative humidity [r.h.]=40%) and suggested that the T es threshold for sweating remained unchanged while SR on the chest and arm in response to increased T es was significantly reduced. Moreover, Mack et al 10) suggested that the reduction in cardiac filling pressure by LBNP reduced SR during exercise. Dodt et al 17) suggested that skin sympathetic nervous activity was reduced by LBNP.…”
Section: Hypovolemiamentioning
confidence: 99%
“…They suggested that hypovolemia significantly increased esophageal temperature (T es ) threshold for cutaneous vasodilation by 0.42°C and decreased the maximal SkBF by 50%. Moreover, Mack et al 10) reported that -40 mmHg of lower body negative pressure (LBNP), a maneuver that reduced the venous return to the heart, suppressed cutaneous vasodilation in response to increased T es during exercise while the cessation of LBNP released the suppression. Similarly, other maneuvers to increase the venous return to the heart; acute blood volume expansion 11) , a supine position 12,13) , headout-of-water immersion 14) , or continuous negative pressure breathing 15) all enhanced cutaneous vasodilation during exercise.…”
Section: Hypovolemiamentioning
confidence: 99%